Translation of trade – related neologisms GENERATING since 1995 from English into Vietnamese - Hoàng, Thị Kiều Mơ (2020)
The thesis is arranged in five main chapters: Introduction, Literature review, Methodology, Findings & Discussion and Conclusion. The paper is aimed to study on how neologisms relating to trade have been translated so far and to offer some strategies to deal with this type of word. Chapter 1 of the paper states the rationale, aims and objectives, significance of the paper. Also, the scope and organization of the paper are mentioned in this chapter. Chapter 2: Literature review studies the theoretical background knowledge the paper relies on. In this chapter, all understandings about neologisms and translation are introduced. Moreover, some previous related studies both in Vietnam and in the world are presented. The chapter 3 focuses on the researched instruments, the procedure of data collection and data analysis procedure. Chapter 4, the main part of the study, analysis and comments on the translation of neologisms relating to trade are carried out. Furthermore, some suggestions for strategies of translating neologisms relating to trade are offered. The last chapter summarizes the whole paper. The chapter 5 also indicates the shortcomings of the study and offers some suggestions for further studies.